HUBUNGAN KADAR VITAMIN B12 IBU HAMIL ANEMIA TRIMESTER III TERHADAP BERAT BADAN BAYI LAHIR - Citra Dewi Anitasari (LPPM Universitas Abdurrab, 2024)
Anemia in pregnancy is a common health problem that occurs in the world, especially in development countries. Anemia during pregnancy due to deficiency of micronutrients such as iron, vitamin B12 and folic acid. Anemia is a condition in which red blood cell (erythrocytes) in blood circulation or hemoglobin mass are unable to fulfill its function as a carrier of oxygen throughout the tissues. Iron is a common cause of anemia but other nutritional iron deficiencies such as vitamin B12, vitamin C, folic acid and vitamin A can also cause anemia. Vitamin B12 deficiency not only triggers anemia but also can disrupt the nervous system. The purpose of this study was to determine the relationship between serum vitamin B12 levels of anemia during pregnancy on newborn birth weight. This is a cross sectional study. The population of study is all anemia during pregnancy who come to Lubuk Buaya Primary Health Care. The sample study that meets inclusion criteria amounting to 40 respondents taken with consecutive sampling technique. Examination of vitamin B12 levels was done in the Biomedical Laboratory of Andalas University by ELISA method. Statistical test using SPSS, Normality test with Shapiro-Wilk and Spearman test to see the relationship between vitamin B12 levels on newborn birth weight. The results showed that vitamin B12 average level of anemia during pregnancy on newborn birth weight 299,53 ± 98,46 with p> 0,05, r = 0,161. The conclusion of study is there is a possitive and not significant correlation between vitamin B12 levels of anemia during pregnancy with newborn birth weight. It is recommended that pregnant women continue to consume Fe tablet during pregnancy and further research to see maternal obedience in consume Fe tablets.